2014
DOI: 10.5120/16332-5612
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Round Robin Concept for Load Balancing Algorithm at Virtual Machine Level in Cloud Environment

Abstract: Day by Day increasing traffic on internet introduces the requirement of load balancing concept to get the most utilization of the resources available on Cloud. There are so many complex calculations and concepts implemented to achieve better and better resource utilization and performance. Out of all this complexity the Rounrobin algorithm provide the simplest solution for load balancing in cloud environment. So we are going to use roun robin as a base algorithm and propose an improved version of load balancin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Modified Active Monitoring algorithm is based on Active monitoring algorithm. The core point of this load Collate algorithm to find the VM with least Load along with the process to allocate free VM to any request so that optimum utilization of the virtual machine is done [11]. It checks the least loaded VM to serve the request simultaneously considering the previous allocation.…”
Section: )Modified Active Monitoring Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…Modified Active Monitoring algorithm is based on Active monitoring algorithm. The core point of this load Collate algorithm to find the VM with least Load along with the process to allocate free VM to any request so that optimum utilization of the virtual machine is done [11]. It checks the least loaded VM to serve the request simultaneously considering the previous allocation.…”
Section: )Modified Active Monitoring Algorithmmentioning
confidence: 99%
“…Which can be deduced by the help of the algorithm execution round? In this algorithm, first of all, ready-queue initialized burst time lists, Time Quantum (TQ), VM-state list, no of rounds [11]. Then allocate the VM to request in the ready queue according to the no.…”
Section: )Fair Round-robinmentioning
confidence: 99%
See 1 more Smart Citation
“…So, we require the accurate solution for overloading problem on different data center for distributing load across multiple data centers. Distributed computing has various advantages for user's requirements and applications (Dave and Maheta, 2014). In centralized data center all load is allocated and scheduled on single data center so this data center is used for sharing cloud network and can apply static and dynamic load balancing approaches.…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, Stuti Dave et al suggested to use the round robin concept for load balancing at virtual machine level in cloud environment [7]. In this paper, the author specifies an improved round robin algorithm that id Fair Round Robin Algorithm that provides simplest solution to load balancing in cloud computing.…”
Section: Existing Load Balancing Algorithms In Cloud Computing Using mentioning
confidence: 99%